The lost years [compact disc, unabridged] - Clark, Mary Higgins (Clark, Mary Higgins. Alvirah and Willy., 2012)
Mariah Lyons risks her life to solve the brutal murder of her father, Dr. Jonathan Lyons, a well-respected academic, who in a stroke of luck comes into the possession of an ancient and highly valuable parchment stolen from the Vatican in the 15th century.